2018
DOI: 10.1038/s41598-018-31082-5
|View full text |Cite
|
Sign up to set email alerts
|

Presence of esterase and laccase in Bacillus subtilis facilitates biodegradation and detoxification of cypermethrin

Abstract: Ubiquitous presence of cypermethrin as a contaminant in surface stream and soil necessitates to develop potential bioremediation methods to degrade and eliminate this pollutant from the environment. A cypermethrin utilizing bacterial strain (MIC, 450  ppm) was isolated from the soil of pesticide contaminated agriculture field and characterized by using polyphasic approach. On molecular basis bacterial isolate showed 98% homology with Bacillus subtilis strain 1D. Under optimized growth conditions, bacteria show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 43 publications
2
83
0
Order By: Relevance
“…We confirmed that strain SG4 produced non-toxic intermediates while effectively degrading cypermethrin. Our results aligned with previous reports on other bacterial strains [28,30,43]. Hydrolysis of cypermethrin was mediated via the cleavage of the ester bond, resulting in the formation of acid and alcohol [1].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We confirmed that strain SG4 produced non-toxic intermediates while effectively degrading cypermethrin. Our results aligned with previous reports on other bacterial strains [28,30,43]. Hydrolysis of cypermethrin was mediated via the cleavage of the ester bond, resulting in the formation of acid and alcohol [1].…”
Section: Discussionsupporting
confidence: 91%
“…B. thuringiensis (Bt) is a bacterium well-known for its broad capabilities and it is widely used in biological control [42]. Bt has been reported for the degradation of cypermethrin and other pyrethroids [17,42,43]. However, the potential use of Bt in the bioremediation of pyrethroid-contaminated environments has not received adequate attention.…”
Section: Discussionmentioning
confidence: 99%
“…One novel approach to enzyme immobilization is based on the entrapment of magnetic nanoparticles via epoxy cross-linking. This technique can be employed to improve the activity of pollutant degradation bacteria, fungi, or heterologous-expressed enzymes (Iype et al, 2017;Gangola et al, 2018). Recent high throughput techniques can be used to explore key functional strains from the pesticide degradation microbial community and fulfill the gap between laboratory cultures and large-scale applications .…”
Section: Novel Technologiesmentioning
confidence: 99%
“…The degradation of cypermethrin is well-studied in some Bacilli including Bacillus sp. SG2 (Pankaj et al, 2016 ), B. subtilis BSF01 (Xiao et al, 2015 ), B. subtilis strain 1D (Gangola et al, 2018 ), Bacillus sp. AKD1 (Tiwary and Dubey, 2016 ), Bacillus sp.…”
Section: Role Of Bacillus Species In Biodegradatiomentioning
confidence: 99%
“…The phenyl ester of o -phenoxy benzoic acid was degraded via the formation of phenol-M-tert-butyl, phenol, and aliphatic hydrocarbons or short-chain compounds. Another pathway of degradation of cypermethrin was studied in B. subtilis strain 1D (Gangola et al, 2018 ). In this pathway, cypermethrin was initially transformed into 3-(2, 2-dichloro ethenyl)-2,2-dimethyl-cyclopropanecarboxylate and cyclododecylamine due to hydrolysis of the ester linkage ( Figure 5 ).…”
Section: Role Of Bacillus Species In Biodegradatiomentioning
confidence: 99%